Reform des Unterhaltsrechts - 5. Göttinger Workshop zum Familienrecht - Lipp, Volker; Schumann, Eva; Veit, Barbara (Universitätsverlag Göttingen, 2007)
The upcoming reform of the law of alimony was subject of the 5th Goettinger Workshop for Family Law on October 9, 2006. This volume allocates the papers of this workshop, including a general view of the conception and the aims of the reform (Gerhard Hohloch) and a legal comparison between German and French divorce law (Thomas Gergen).